De Novo Mutations in the Motor Domain of KIF1A Cause Cognitive Impairment, Spastic Paraparesis, Axonal Neuropathy, and Cerebellar Atrophy. Issue 1 (27th November 2014) - Lee, Jae‐Ran; Srour, Myriam; Kim, Doyoun; Hamdan, Fadi. F.; Lim, So‐Hee; Brunel‐Guitton, Catherine; Décarie, Jean‐Claude; Rossignol, Elsa; Mitchell, Grant A.; Schreiber, Allison; Moran, Rocio; Van Haren, Keith; et al.
<x xml:space="preserve">Abstract</x> De novo (genetic changes not transmitted from the parents) missense mutations targeting conserved residues in the motor domain of the neuron‐specific motor protein KIF1A alters its activity and cause a complex neurologic phenotype characterized by severe developmental delay and/or intellectual disability, as well as variable cerebellar atrophy, visual loss, spastic paraparesis, peripheral neuropathy and epilepsy. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>